Diversity of sandflies (Psychodidae: Phlebotominae) captured in sandstone caves from Central Amazonia, Brazil - Veracilda Ribeiro Alves; Rui Alves de Freitas; Francisco Lima Santos; Toby Vincent Barrett (Memorias do Instituto Oswaldo Cruz, 2011)
In the present paper we describe the diversity of phlebotomine sandflies collected in three sandstone caves in the municipality of Presidente Figueiredo, state of Amazonas, Brazil. The phlebotomines were captured during 2006 with CDC light traps. Guano samples from inside the Gruta Refúgio do Maruaga were collected to investigate the presence of immature specimens. A total of 2,160 adult phlebotomines representing 15 species were captured. Pintomyia pacae was the dominant species in Gruta dos Animais (1,723 specimens) and Gruta dos Lages (50 specimens) and Deanemyia maruaga new comb (280 specimens) was the dominant species in Gruta Refúgio do Maruaga. A total of 18 guano samples were collected and seven of these samples included immature specimens. A total of 507 immature specimens were captured; 495 of these specimens were larvae and 12 were pupae. The presence of paca (Agouti paca) footprints near Gruta dos Animais and Gruta dos Lages suggests the association of Pi. pacae with this rodent. This finding may explain the abundance of Pi. pacae in these locations, while the species is relatively rare in the forest. Deanemyia maruaga is a cave species that uses guano to breed during its immature stages. Adult specimens of this species are apparently parthenogenetic and autogenous and represent the second record of parthenogenesis for the subfamily Phlebotominae.